The is and moral ought of intersubjectivity - Mabaquiao, Napoleon M. (Animo Repository, 2017)
The paper analyzes the possibility and moral normativity of intersubjectivity - here understood as referring to the kind of human interaction that respects the personhood of human beings. The analysis of the possibility of intersubjectivity inquires into the conditions of its occurrence; while the analysis of its moral normativity examines the basis of its status as a moral obligation. The paper advances two points. The first is the distinction between theoretical intersubjectivity, where persons are perceived or conceived as subjects and not as objects, and practical intersubjectivity, where persons are treated as ends and not merely as means. The second is the clarification that the imperativity of theoretical intersubjectivity (for involving perceptions and beliefs about persons) is epistemic while that of practical intersubjectivity (for involving intentions and actions towards persons) is moral. Given these points and the questionable status of the possibility of theoretical intersubjectivity (for requiring a nonconceptual knowledge of persons), confusing the latter with practical intersubjectivity would render the morality of intersubjectivity problematic. © 2017 Journal of Dharma: Dharmaram Journal of Religions and Philosophies.